2015
DOI: 10.1002/qre.1797
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Future Directions for Quality Engineering

Abstract: The origins of quality engineering are in manufacturing, where quality engineers apply basic statistical methodologies to improve the quality and productivity of products and processes. In the past decade, people have discovered that these methodologies are effective for improving almost any type of system or process, such as financial, health care, and supply chains.This paper begins with a review of key advances and trends within quality engineering over the past decade. The second part uses the first part a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 63 publications
(85 reference statements)
0
24
0
Order By: Relevance
“…Control limits are determined at a given ARL 0 . Moreover, the Fredholm integral equation of the second kind is used to numerically compute the ARL 1 .…”
Section: Existing Control Charts For Complete Data and Type-ii Censmentioning
confidence: 99%
See 1 more Smart Citation
“…Control limits are determined at a given ARL 0 . Moreover, the Fredholm integral equation of the second kind is used to numerically compute the ARL 1 .…”
Section: Existing Control Charts For Complete Data and Type-ii Censmentioning
confidence: 99%
“…Recently, Vining et al suggested that there is a strong need to develop process control techniques for reliability data to ensure that the product/process maintains the expected reliability standard. Li and Kong noted that the techniques which have been proposed to monitor the occurrence rate of nonconforming items can be viewed as monitoring failure events.…”
Section: Introductionmentioning
confidence: 99%
“…In the food industry, quality characteristics include sensory properties such as flavor, color, aroma, taste, and texture; quantitative properties namely, percentage of a certain ingredient, weight, length and width of a certain product, etc . Vining et al stated that the food industry is a potential area for the application of statistical process improvement approaches. Statistically monitoring food quality characteristics is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Greater emphasis on reliability is one of the future directions for quality engineering . Vining et al .…”
Section: Introductionmentioning
confidence: 99%
“…Greater emphasis on reliability is one of the future directions for quality engineering. 5 Vining et al 6 noted that current practice almost exclusively restricts the use of experimental protocols in reliability testing to completely randomized accelerated life tests. The future will see more broad scale use of basic experimental designs, analyses, protocols, and concepts.…”
Section: Introductionmentioning
confidence: 99%